Comparison of systematic roost searches and acoustic detection to determine occupancy of rare forest bats. (11th December 2013) - Comer, Christopher E.; Stuemke, Leigh A.; Morrison, Michael L.; Maxey, Ricky W.
ABSTRACT Despite recent increases in conservation interest, the distribution, habitat needs, and conservation priorities remain poorly understood for many animal species, including forest bats. In some cases, little quantitative information exists about appropriate survey methods to determine occupancy or abundance of bats in forest systems. We quantitatively compared detection probabilities between 2 commonly used survey techniques for 2 bat species that are closely associated with bottomland hardwood stands in the southeastern United States. Passive acoustic surveys of echolocation calls were more likely than systematic roost searches to detect both Rafinesque's big‐eared bats (Corynorhinus rafinesquii) and southeastern myotis (Myotis austroriparius) at 7 study areas in eastern Texas. Our results confirmed that numerous repeat visits (>15 acoustic‐survey‐nights) are necessary to have high confidence in detecting Rafinesque's big‐eared bats; however, southeastern myotis were easier to detect. Our results emphasize the importance of quantitatively assessing survey methods prior to designing or implementing widespread survey programs for bats. © 2013 The Wildlife Society